Middle Eastern Monarchies: Ingroup Identity and Foreign Policy Making - Sunik, Anna (Routledge Studies in Middle Eastern Politics Ser., 2020)
Cover -- Half Title -- Series -- Title -- Copyright -- Dedication -- Contents -- List of tables and figures -- List of abbreviations and glossary -- 1 Introduction: explaining the dynamics of "monarchic peace" -- 2 Moving beyond democratic exceptionalism: the peace among similar political systems -- 3 Middle East monarchies from the Arab Cold War to the Arab Spring -- 4 When monarchies collide: case studies of "near misses" of monarchic war -- 5 From monarchy to republic - from peace to war?: "Quasi-experiments" of collapsed monarchic couples -- 6 The limits of SPSP: deviant cases? -- 7 Conclusion: toward a peace among similar political systems -- Index.